2021
DOI: 10.3389/fcell.2021.666387
|View full text |Cite
|
Sign up to set email alerts
|

The CAGE–MiR-181b-5p–S1PR1 Axis Regulates Anticancer Drug Resistance and Autophagy in Gastric Cancer Cells

Abstract: Cancer-associated gene (CAGE), a cancer/testis antigen, has been known to promote anticancer drug resistance. Since the underlying mechanisms of CAGE-promoted anticancer drug resistance are poorly understood, we established Anticancer drug-resistant gastric cancer cells (AGSR) to better elucidate possible mechanisms. AGSR showed an increased expression level of CAGE and autophagic flux compared with anticancer drug-sensitive parental gastric cancer cells (AGS cells). AGSR cells showed higher invasion potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Several studies have already reported the activation of diverse biological processes via experimental results or bioinformatic analysis. Yeon et al 6 reported that the miR-181b-5p/CAGE/S1PR1 axis can alter autophagic flux, resulting in enhanced sensitivity to anticancer drugs. Wang et al 7 revealed that cisplatin resistance was transmitted by the exosomal lncRNA HOTTIP, which targets the miR-218/HMGA1 axis in cisplatin-sensitive cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already reported the activation of diverse biological processes via experimental results or bioinformatic analysis. Yeon et al 6 reported that the miR-181b-5p/CAGE/S1PR1 axis can alter autophagic flux, resulting in enhanced sensitivity to anticancer drugs. Wang et al 7 revealed that cisplatin resistance was transmitted by the exosomal lncRNA HOTTIP, which targets the miR-218/HMGA1 axis in cisplatin-sensitive cells.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we further investigated the possible mechanism underlying the regulative effect of FEZF1-AS1 on chemoresistance of GC cells. Several previous studies had reported that enhanced autophagy is one of the important mechanisms of increased chemo-resistance in several tumor cells including GC cells ( Yuan et al, 2016 ; Pei et al, 2018 ; Yeon et al, 2021 ). Therefore, we hypothesized that FEZF1-AS1 can regulate chemoresistance in GC cells via modulating autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells may induce autophagy for survival in response to anti-cancer drugs [ 100 , 101 ]. Autophagy is positively associated with anti-cancer drug resistance [ 102 , 103 ]. The activation of phosphoinositide 3 (PI3K)/Akt signaling promoted autophagy and chemotherapy resistance in breast cancer cells [ 104 ].…”
Section: Role Of the Mir-200 Family In Anti-cancer Drug Resistancementioning
confidence: 99%